Evaluating the effect of extension techniques on the adoption of conservation agriculture in semi arid communal wards 8, 10, 11 and 19 of Shurugwi district in Midlands province, Zimbabwe - Mabaya, Sipiwe (Midlands State University, 2017)
A survey was carried out to evaluate the effect of extension techniques on the adoption of conservation agriculture. This was done through determining the effect of farmers’ knowledge and challenges they face in practicing conservation agriculture in a bid to increase adoption of conservation agriculture. Literature was gathered on conservation agriculture and extension techniques from books, internet, journals and periodicals. Primary data was collected from communal areas of Shurugwi district where conservation agriculture was being practiced. Four out of ten wards were selected using stratified random sampling method with the wards as strata. The selected wards had a total of 945 farmers practicing conservation agriculture. Only 11% (105) of these farmers were selected as a sample. The data was collected using structured questionnaire and focused group discussions. The data were analysed using SPSS version 20. Chi-Square test was used to test association between variables. The variables tested were knowledge against adoption and extension methods against knowledge. The results showed that knowledge of farmers has significant effect on the adoption of conservation agriculture. They also highlighted that extension methods used to disseminate information have a significant effect on knowledge of the farmers. However the results showed that extension methods do not affect the adoption of CA. Therefore, the study concluded that besides extension methods there are many other factors that influence the adoption of CA among which are challenges of mulch gathering, basin digging and buying of fertilisers. It was thus recommended that farmers be provided with cheaper tools and machinery, use of manure and be encouraged to gather mulch in summer so that the challenges they face might be lessened. Further research is still needed on CA equipment that can be made locally. Further research needs to be done at district level so as to note the challenges faced by farmers in every district.